DETERMINANTS OF ACCOUNTING STANDARD STATEMENT (PSAK) 69 IN INDONESIA (BIOLOGICAL ASSETS IN PLANTATION AND CORPS SUB-INDUSTRY COMPANIES LISTED ON IDX IN 2020-2022) - Nurvinka Renata; Aminah; Haninun (ZILLZELL MEDIA PRIMA, 2024)
The development of companies in agriculture is supported by the availability of information that is also taken into consideration for decision making by company owners or company management. The purpose of this study is to determine the impact of biological asset intensity, type of auditor, and public ownership on biological asset disclosure. Therefore, the company's annual report must contain as much information as possible. Agricultural companies are required to disclose their biological assets under PSAK 69. However, many agricultural companies have not disclosed their biological assets in full. The focus of his research was to observe how the intensity of biological assets, the type of KAP auditor, and public ownership affect the disclosure of biological assets. The population of this study is plantation & food crop companies listed on the Indonesia Stock Exchange (IDX) 2020-2022 which amounts to 20 entities. 19 out of 20 companies. The study sample was taken using the purposive sampling method. The research technique uses panel data regression on SPSS. The results of this study are the intensity of biological assets, the type of KAP auditor, public ownership has a significant positive influence on the disclosure of biological assets.